Rab11a Regulates the Development of Cilia and Establishment of Planar Cell Polarity in Mammalian Vestibular Hair Cells - Bin-Jun Chen (Frontiers Media S.A., 2021)
Vestibular organs have unique planar cell polarity (Figure 1A), and their normal development and function are dependent on the regular polarity of cilia (Figure 1B) requires. Rab11a is a small G protein that participates in the transportation of intracellular and extracellular materials required for polarity formation; however, our understanding of the mechanisms of the actions of Rab11a in vestibular organs is limited. Here, we showed that the general shape of the utricle was abnormal in Rab11aCKO/CKO mice. These mice also showed abnormal morphology of the stereocilia bundles, which were reduced in both length and number, as well as disturbed tissue-level polarity. Rab11a affected the distribution of polarity proteins in the vestibular organs, indicating that the normal development of cilia requires Rab11a and intraflagellar transportation. Furthermore, small G protein migration works together with intraflagellar transportation in the normal development of cilia. FIGURE 1Morphological changes of stereocilia in the extrastriolar hair cells from Rab11a single or Rab11a/IFT88 double-mutant utricles. (A) Medial view of a mouse left inner ear with its five vestibular sensory organs (gray). Enlarged are the utricle showing their subdivisions, LPR (yellow line), and striola (blue). LES, lateral extrastriola; MES, medial extrastriola; LPR, line of polarity reversal. (B) Schematic view of vestibular hair cell. Kinocilium is marked with ace-tubulin. Basal body is marked with γ-tubulin. (C,C1,D,D1) Normal appearance of the stereocilia of extrastriolar hair cells of wild-type controls. (E,E1,F,F1) Altered morphology in Rab11aCKO/CKO animals. (G,G1,H,H1) The changes in the stereocilia morphology were more severe in Rab11aCKO/CKO/IFT 88CKO/+ mice. (I–L) Higher magnification of confocal images of hair cells. (M–P) Scanning electron microscopy images of hair cells from wild-type controls and Rab11a mutants. (I,M) Morphology of normal. hair cells of wild-type controls. (J,N) The number of stereocilia on a single hair cell was deceased in the Rab11a mutant. (K,O) Stereocilia were shorter in mutants compared to the wild-type controls. (L,P) The staircase-like hair bundle architecture of hair cells was lost in Rab11a mutant mice. (Q) The percentage of hair cells with abnormal development of static cilia bundles in the extrastriola region was counted as a percentage of the total (n = 5). The percentage of abnormal hair cells was higher in Rab11aCKO/CKO, IFT88CKO/+ mice compared to Rab11aCKO/CKO. The abnormal ratios of single and double knockout hair cells were 42.1 ± 5.7 and 71.5 ± 10.4, respectively. In (A–J), for all primary panels, hair cell stereociliary bundles were marked with phalloidin (green), the actin-rich cuticular plate of hair cells was labeled with β-spectrin (red), while the basal body of the hair cell was labeled with γ-tubulin (blue). Scale bars: 10 μm (C–H1), 5 μm (J–N). *P < 0.05.